WACANA PEMBERITAAN SUARA KORBAN KEKERASAN SEKSUAL DALAM PERSPEKTIF STANDPOINT THEORY - Triyani, Siti; Widiastuti, Wahyu; Perdana, Dionni Ditya (Journal of Gender and Social Inclusion in Muslim Societies, 2023)
AbstractSexual violence is still a frightening scourge for women, but women's voices in sexual violence cases are still often sidelined. The purpose of this study is to describe the discourse of reporting the voices of victims of sexual violence in the perspective of standpoint theory. This study used Norman Fairclough's critical discourse analysis with descriptive qualitative research methods. The data collection techniques used are observation, documentation, and interviews. The findings of this study show that the series of news voices of victims of sexual violence reported in bengkuluekspress.com in the text dimension displays representations of resistance, the identity of victims of sexual violence, and social relations. In the practice discourse dimension, news production carried out bengkuluekspress.com, news dissemination, and text consumption can help readers to understand how news about rape and sexual violence cases can influence public views and provide a more complete picture of the impacts of these cases. Furthermore, in the socio-cultural dimension, bengkuluekspress.com delivered a discourse of criticism of the community, law enforcement officials, and the government, especially institutions that shelter women, in highlighting cases of sexual violence against women in order to realize a Bengkulu Province free of sexual violence. AbstrakKekerasan seksual masih menjadi momok menakutkan bagi perempuan, namun suara perempuan dalam kasus kekerasan seksual masih sering dikesampingkan. Tujuan dari penelitian ini adalah untuk mendeskripsikan wacana pemberitaan suara korban kekerasan seksual dalam perspektif standpoint theory. Penelitian ini menggunakan analisis wacana kritis Norman Fairclough dengan metode penelitian kualitatif deskriptif. Teknik pengumpulan data yang digunakan yakni observasi, dokumentasi, dan wawancara. Temuan penelitian ini menunjukkan bahwa rangkaian berita suara korban kekerasan seksual yang diberitakan di bengkuluekspress.com dalam dimensi teks menampilkan representasi perlawanan, identitas korban kekerasan seksual, dan relasi sosial. Dalam dimensi practice discourse, produksi berita yang dilakukan bengkuluekspress.com, penyebaran berita, dan konsumsi teks dapat membantu pembaca untuk memahami bagaimana berita tentang kasus pemerkosaan dan kekerasan seksual serta dapat memengaruhi pandangan masyarakat dan memberikan gambaran yang lebih lengkap tentang dampak-dampak dari kasus tersebut. Selanjutnya, dalam dimensi socio-cultural, bengkuluekspress.com menyampaikan wacana kritik terhadap masyarakat, aparat penegak hukum, dan pemerintah pemerintah khususnya lembaga yang menaungi perempuan, dalam menyoroti kasus kekerasan seksual terhadap perempuan dalam rangka mewujudkan Provinsi Bengkulu yang bebas kekerasan seksual.